جدليةالتقليدي والحداثي - فكروني, زاوي (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
كان الهدف من هذه المداخلة هو إعادة قراءة لأحدى دعائم المشروع الانثربولوجي الذي اقترحه "جمال غريد"، هذا الاخير الذي يرتكز على مفهوم مركزي هو"الثنائية الثقافية". فبالنسبة له المجتمع الجزائي هو مجتمع ثنائي: حداثي وتقليدي، وكل المحاولات التي طبقت لتحديثه فشلت، بل كانت لها نتائج عكسية. أكيد أن هذه الثنائية هي ثقافية  بالمعنى الانثربولوجي الصريح، لكنها تتمظهر بوضوح من خلال الأفعال اليومية للافراد والجماعات الاجتماعية. وبالرغم من أن "جمال غريد" قد استعار المفهوم من تخصصات أخرى مثل الفلسفة وعلم الاجتماع والانثربولوجيا، إلا أنه أصبغ عليها لمسة المحلي لكي يطبقها في بحوثه الميدانية التي أجراها على قطاع واسع من مجالات الحياة الاجتماعية. وهو الامر الذي يجعلنا نجزم أنه ساهم في مسعى The objective thatweaimthroughthis communication aims to question on one of the foundations of anthropologicalprojectproposed by Djamel Guerid ,thisprojectwhichisessentiallybased on the concept of "cultural duality." For him the Algerian society is double: modernist and traditionalistthat efforts to impose the modernist society have in factproduced the opposite. Certainly, itis cultural in the anthropologicalsense of the term, but itisclearlymanifestedthrough the daily action of individuals and social groups. Recalling. Rightly, itis réapproprié this concept belonging to the philosophical traditions, sociological and anthropological, to better the redefine and apply in itsempiricalstudies on a widevariety of objects. Wherewecansaythatit has participated in the attempt of the foundation of a local épistémè .This épistémè whichwe are lacking in the Arab world. This approachfits in the constitutive movement and of cumulative scientific productions in the field of anthropology in Algeria. It is a desire to base an anthropology of practice guided by a vision the epistemologicalsharpened and revisit, in view of the creation of a new anthropologywhichwouldbebreakingwithwhatwascurrent and conventional.